1992
DOI: 10.1093/nar/20.21.5647
|View full text |Cite
|
Sign up to set email alerts
|

Alteration by site-directed mutagenesis of the conserved lysine residue in the consensus ATP-binding sequence of the RecB protein ofEscherichia coli

Abstract: The RecB and RecD subunits of the RecBCD enzyme of Escherichia coli contain amino acid sequences similar to a consensus mononucleotide binding motif found in a large number of other enzymes. We have constructed by site-directed mutagenesis a lysine-to-glutamine mutation in this sequence in the RecB protein. The mutant enzyme (RecB-K29Q-CD) has essentially no nuclease or ATP hydrolysis activity on double-stranded DNA, showing the importance of RecB for unwinding double-stranded DNA. However, ATP hydrolysis stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…DNA substrates with short 3Ј-overhangs or blunt duplex ends are barely unwound at all (Fig. 3, green traces), in agreement with the published observations (29,33). However, the presence of just two additional ssDNA nucleotides on the 5Ј-strand (NdeI-cut substrate) is sufficient to reveal a rapid and processive helicase activity that is further enhanced if there are four ssDNA nucleotides on the 5Ј-terminated strand (EcoRI-cut substrate).…”
Section: K177qsupporting
confidence: 89%
See 2 more Smart Citations
“…DNA substrates with short 3Ј-overhangs or blunt duplex ends are barely unwound at all (Fig. 3, green traces), in agreement with the published observations (29,33). However, the presence of just two additional ssDNA nucleotides on the 5Ј-strand (NdeI-cut substrate) is sufficient to reveal a rapid and processive helicase activity that is further enhanced if there are four ssDNA nucleotides on the 5Ј-terminated strand (EcoRI-cut substrate).…”
Section: K177qsupporting
confidence: 89%
“…2C) CD enzyme had suggested that the enzyme did not possess ATPase activity on duplex DNA substrates and, consequently, that it was probably not a DNA helicase (29,33). However, those studies only employed plasmid DNA substrates that had been linearized with restriction enzymes that generate blunt ends or short 3Ј-overhangs.…”
Section: K177qmentioning
confidence: 99%
See 1 more Smart Citation
“…These protein caps are thought to block RecBCD binding and subsequent exonucleolytic degradation (Oliver and Goldberg 1977), so that T4 2 + but not T4 2 2 phage form plaques on RecBCD nucleaseproficient strains. Wild type and all RecC tunnel mutants reported here were RecBCD nuclease-proficient by this assay; indicating that RecBCD enzyme was functionally intact, at least for nuclease activity, which requires the helicase and ATPase activities (Hsieh and Julin 1992;Yu et al 1998). Chi activity and recombination proficiency were measured using l red gam mutant phage.…”
mentioning
confidence: 78%
“…However, the effect of these Lys 464 mutations on opening rate is relatively small (2-4-fold), compared with the large (1-2 orders of magnitude) effect of the analogous mutation in NBF2 (Lys 1250 ) on open burst duration. Furthermore, the large effect of mutations in the corresponding invariant "P-loop" lysines on the hydrolysis rate of other GTPases and ATPases (35)(36)(37) indicates that the hydrolysis rate of Lys 464 mutants is likely to be very low. This discrepancy between the predicted hydrolysis rate and the effect on channel gating led us to propose that ATP hydrolysis at NBF1, while essential for CFTR activity, is not directly coupled to the initiation of each open burst (15).…”
Section: Discussionmentioning
confidence: 99%